2018
DOI: 10.1111/ane.12948
|View full text |Cite
|
Sign up to set email alerts
|

The increasing prevalence of Parkinson's disease in Estonia

Abstract: The age-specific crude rates in oldest age-groups have risen substantially, and the age-adjusted prevalence has moderately increased compared to 20 years ago in Estonia. We hypothesize that the increased life expectancy of the Estonian population and improved diagnosis of PD contributed most to the increase in disease frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…1 We read with great interest the papers cited in this letter that investigate the comorbidity and mortality of PD, paying a special attention to the cardiac abnormalities, in particular, the sudden unexpected death in PD (SUDPAR). 1 We read with great interest the papers cited in this letter that investigate the comorbidity and mortality of PD, paying a special attention to the cardiac abnormalities, in particular, the sudden unexpected death in PD (SUDPAR).…”
Section: Response To the Letter By Scorza Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…1 We read with great interest the papers cited in this letter that investigate the comorbidity and mortality of PD, paying a special attention to the cardiac abnormalities, in particular, the sudden unexpected death in PD (SUDPAR). 1 We read with great interest the papers cited in this letter that investigate the comorbidity and mortality of PD, paying a special attention to the cardiac abnormalities, in particular, the sudden unexpected death in PD (SUDPAR).…”
Section: Response To the Letter By Scorza Et Almentioning
confidence: 99%
“…
We appreciate the letter from Dr Scorza and his colleagues regarding our recently published article "The increasing prevalence of Parkinson's disease (PD) in Estonia." 1 We read with great interest the papers cited in this letter that investigate the comorbidity and mortality of PD, paying a special attention to the cardiac abnormalities, in particular, the sudden unexpected death in PD (SUDPAR).Based on the World Health Organization reports, the increase in mean life expectancy at birth for Estonian people has been remarkable, rising from 70.8 years in 2000 to 77.6 years in 2015. The shift towards longer life expectancy has increased more rapidly in Estonia than in the European region in general where the above-mentioned indicator has risen from 73 years in 2000 to 77.1 years in 2015.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Estonia lies in the North-Eastern part of Europe and has a population of about 1.3 million. The age-adjusted prevalence of PD is 314/100 000 5 so there are about 4000 PD patients in Estonia.…”
mentioning
confidence: 99%
“…4 The authors concluded that increased life expectancy of the Estonian population and improved diagnosis of PD contributed most to the increase in disease frequency. 4 The authors are correct in their reflections, but this leads us to another point that may determine the prevalence of PD: Mortality of PD, which is still little explored in the literature and not frequently discussed in the neuroscientific community. 3 It is clear that PD is not considered a "fatal disease," but one of the ten most frequently asked questions about PD is as follows:…”
mentioning
confidence: 99%